Clarification on quotation for additional wall attached to diaphragm wall of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding clarification on quotation for additional wall attached to diaphragm wall of BRAC University new campus project.